2014
DOI: 10.4314/ahs.v13i4.42
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriological and physico-chemical quality of drinking water sources in a rural community of Ethiopia

Abstract: Background: Accesses to safe water is a universal need however, many of the world's population lack access to adequate and safe water. Consumption of water contaminated causes health risk to the public and the situation is serous in rural areas. Objectives: To assess the bacteriological and physico-chemical quality of drinking water sources in a rural community of Ethiopia. Methods: Water samples were collected from tap, open springs, open dug wells and protected springs for bacteriological analysis of total c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 15 publications
9
39
0
Order By: Relevance
“…This finding is in agreement with a study conducted in rural communities of Ethiopia (Amenu et al, 2014;Tsega et al, 2013). They reported that All dug wells and springs were at high risk category for total coliforms.…”
Section: Discussionsupporting
confidence: 92%
“…This finding is in agreement with a study conducted in rural communities of Ethiopia (Amenu et al, 2014;Tsega et al, 2013). They reported that All dug wells and springs were at high risk category for total coliforms.…”
Section: Discussionsupporting
confidence: 92%
“…Samples collected from protected hand dug wells and developed springs located in the rural areas of Ethiopia showed that many wells have high level of E. coli [12] [13]. Similarly, a rapid assessment of drinking water quality in Ethiopia showed that the nitrate and fluoride concentration of more than 30% of water sources exceeded the WHO drinking water quality standards [14].…”
Section: Introductionmentioning
confidence: 99%
“…Hedging the premises adequately, enhancing regular maintenance and disposing correctly human and animal wastes (which infiltrate the soil and contaminate the place) are mandatory. They are strategies that ensure the safety of the water sources (Tsega et al, 2013;Bain et al, 2014).…”
Section: Microbiological Assessmentmentioning
confidence: 99%